Demographic Factors and Cholera in Thailand, 2007 - Chongthawonsatid, Sukanya; Rattanadilok Na Bhuket, Ponchanok (Journal of Health Science of Thailand, 2018)
This descriptive study was using data collected by surveillance report on cholera in 2007 from the Bureau of Epidemiology. Sample of this study was 1,364 cholera patients. Data were analyzed using percentage and chi-square. Results indicated that cholera patients were found in male more than female aged < 14 years; however, cholera female patients were found in greater number than male aged 15-24 years. Most of cholera patients lived in the Northeast, South, North, and Central regions, respectively. Furthermore, age, sex and region factors were significantly related to the morbidity of cholera (p<0.05). These findings suggest that preventive measures on cholera, which focus on host and environment components like knowledge and mass media, should be provided appropriately taking into account sex, age, social context, environment in family and community.